The Role of Wikipedia on Corporate E-Reputation: Evidence from French Companies. Issue 1 (2nd January 2017) - Khelladi, Insaf; Boutinot, Amelie
Abstract: This study complements previous research on e-reputation by exploring how social media influence corporate e-reputation by extending the circle of stakeholders who can influence, even indirectly, a company's e-reputation. We also suggest a new way of measuring corporate e-reputation and its determinants. We quantitatively analyze the effect of Wikipedia and its key features on the corporate e-reputation of companies that are listed on the French stock market SBF 120®. Our results show that Wikipedia has an impact on corporate e-reputation across several dimensions, including the articles' quality and reputation, the latter resulting from a combination of the authors' rigor and diversity, and the immediacy of information provision.